Prism Adaptation Treatment of Spatial Neglect: Feasibility During Inpatient Rehabilitation and Identification of Patients Most Likely to Benefit - Gillen, Robert W.; Harmon, Erin Y.; Weil, Brittany; Fusco-Gessick, Benjamin; Novak, Paul P.; Barrett, A. M. (Frontiers in Neurology, 2022)
Objective: Spatial Neglect is prevalent among stroke survivors, yet few treatments have evidence supporting efficacy. This study examines the feasibility of Prism Adaptation Treatment (PAT) within an inpatient rehabilitation facility and the degree by which PAT improves symptoms of spatial neglect and functional independence among sub-acute survivors of right hemispheric stroke. Design: In this retrospective cohort study, 37 right hemispheric stroke patients were identified as having received at least 4 PAT sessions during their inpatient stay. Spatial neglect and functional independence levels of patients in the PAT cohort were compared to a matched active control group comprised of rehabilitation patients receiving alternative therapies to address neglect admitted during the same time period. Results: Most patients received the full recommended 10 sessions of PAT (average sessions completed = 8.6). A higher percentage of severe neglect patients receiving PAT (69%) displayed clinically significant gains on FIM (≥22 points) compared to those receiving alternative treatments (6%). Patients with mild or moderate neglect in the PAT cohort did not exhibit greater benefit than controls. Conclusion: Provision of PAT for treatment of spatial neglect in right hemispheric stroke patients was feasible during the inpatient rehabilitation admission. Patients with severe neglect showed the most benefit from PAT. This study was registered as a retrospective observational study on Clinical Trials.Gov. NCT04977219